A COMPARATIVE ANALYSIS OF EUROPEAN EDUCATIONAL PROGRAMS IN THE LATE 80’S AND EARLY 90’S: COMETT, ERASMUS, PETRA, LINGUA, TEMPUS, AND EUROTECNET - Costel COROBAN; Cristina-Iulia MARINESCU (GÎLĂ) (Annals of the "Ovidius" University of Constanţa. Political Science Series)
This study delves into the impact of key European educational programs launched between the late 1980s and early 1990s, namely COMETT, Erasmus, PETRA, Lingua, TEMPUS, and Eurotecnet. These initiatives represented a concerted effort to foster deeper cooperation within the European Community, focusing on enhancing educational and vocational training opportunities. The COMETT program was instrumental in connecting academia with the labor market and advancing technology training but did not adequately support vulnerable groups such as women, ethnic minorities, and the unemployed. ERASMUS and PETRA contributed significantly to student mobility and youth vocational training, though PETRA struggled to directly address rising youth unemployment. LINGUA focused on enhancing foreign language skills, vital for fostering European integration, while TEMPUS facilitated educational reforms in post-communist Central and Eastern Europe. EUROTECNET promoted innovation in vocational training by integrating new technologies but faced challenges related to consistency across member states. Despite these initiatives’ successes in modernizing the educational systems and enhancing European competitiveness, many programs prioritized economic and technological objectives over social inclusion. Vulnerable groups often remained underrepresented in these reforms. However, these early efforts laid the groundwork for later programs like Leonardo da Vinci and SOCRATES, which aimed to balance competitiveness with social equity. The article calls for further research on the human impact of these programs, particularly regarding youth unemployment and the inclusion of marginalized groups.